“Be a Miner”: Constructions and Contestations of Masculinity in the British Coalfields, 1975–1983 - Gildart, Keith; Curtis, Ben; Perchard, Andrew; Millar, Grace (International review of social history, 2024)
In 1975, the National Coal Board (NCB) produced a short film, “People Will Always Need Coal”, to encourage recruitment into mining. It was extraordinarily attention-grabbing, presenting miners as cosmopolitan playboys. It defined the industry in hyper-masculine terms, encouraging would-be recruits to “be a miner”. This article uses the film as a starting point for a discussion of the complex interactions between the material realities of masculinity, class, and culture within Britain's coalfields in the period 1975–1983. A critical reading of the film is complemented by archival research and oral testimony drawn from interviews with 96 former miners and their families. At a time when the industry was positioning itself as an employer with a long-term future, mining was presented on screen as a modern masculine occupation that was far removed from the dominant imagery of coal for much of the twentieth century. The National Union of Mineworkers’ (NUM) victories in the strikes of 1972 and 1974, the drafting of a Government Plan for Coal, and rising living standards, created a short period of optimism before the cataclysmic closures of the 1980s and 1990s. This was a time when masculinity in the coalfields was being reproduced, modified, contested, and subverted. The years 1975–1983 offer valuable insight into such masculinity and the ways it was mediated and challenged through work, the domestic sphere, leisure, and popular culture.